Efficacy and Safety of Adjunctive Corticosteroids in Non-HIV Pneumocystis jirovecii Pneumonia with Respiratory Failure: A Systematic Review and Meta-Analysis of Randomized and Observational Studies - Reza Rahmadinata; Rohani Lasmaria (HM Publisher, 2026)
Background: Pneumocystis jirovecii pneumonia in HIV-negative immunocompromised patients carries a mortality rate significantly higher than in the HIV-positive population. While adjunctive corticosteroids are the standard of care for HIV-associated pneumonia to prevent Immune Reconstitution Inflammatory Syndrome, their efficacy in non-HIV patients remains controversial due to differing immunopathogenesis. This study evaluated the efficacy and safety of adjunctive corticosteroids in non-HIV patients with respiratory failure, specifically addressing the discordance between historical observational data and recent randomized evidence. Methods: We conducted a systematic review and meta-analysis in accordance with PRISMA guidelines, searching databases from January 2014 to July 2025. We included randomized controlled trials and observational studies of non-HIV adults with pneumonia receiving adjunctive corticosteroids. To address methodological heterogeneity, we performed stratified analyses separating randomized trial data from observational cohorts and conducted sensitivity analyses to account for outliers. Risk of bias was assessed using Cochrane RoB-2 and the Newcastle-Ottawa Scale. Results: Ten studies comprising 2,900 patients were analyzed. The randomized trial demonstrated no statistically significant reduction in 28-day mortality with corticosteroids (21.5% vs 32.4%, p=0.069). In the observational arm, initial pooled analysis suggested benefit, but sensitivity analysis removing a large administrative database study shifted the result to null. Crucially, higher cumulative steroid doses were associated with increased 90-day mortality (Hazard Ratio 1.01 per 100mg equivalent; p<0.05) and a significantly increased risk of secondary infections and hyperglycemia. Subgroup analysis revealed no benefit for pulse-dose regimens over standard dosing. Conclusion: Unlike in HIV, adjunctive corticosteroids do not confer a consistent survival benefit in non-HIV Pneumocystis pneumonia and are associated with dose-dependent toxicity. The routine use of corticosteroids should be abandoned in favor of a cautious approach restricted to severe, early hypoxemia using standard rather than pulse doses.